Integrated Transcriptomics and Metabolomics Analysis Reveal Key Metabolism Pathways Contributing to Cold Tolerance in Peanut - Wang, Xin; Liu, Yue; Han, Zhongkui; Chen, Yuning; Huai, Dongxin; Kang, Yanping; Wang, Zhihui; Yan, Liying; Jiang, Huifang; Lei, Yong; Liao, Boshou (Frontiers in Plant Science, 2021)
Low temperature (non-freezing) is one of the major limiting factors in peanut (Arachis hypogaea L.) growth, yield, and geographic distribution. Due to the complexity of cold-resistance trait in peanut, the molecular mechanism of cold tolerance and related gene networks were largely unknown. In this study, metabolomic analysis of two peanut cultivars subjected to chilling stress obtained a set of cold-responsive metabolites, including several carbohydrates and polyamines. These substances showed a higher accumulation pattern in cold-tolerant variety SLH than cold-susceptible variety ZH12 under cold stress, indicating their importance in protecting peanut from chilling injuries. In addition, 3,620 cold tolerance genes (CTGs) were identified by transcriptome sequencing, and the CTGs were most significantly enriched in the “phenylpropanoid biosynthesis” pathway. Two vital modules and several novel hub genes were obtained by weighted gene co-expression network analysis (WGCNA). Several key genes involved in soluble sugar, polyamine, and G-lignin biosynthetic pathways were substantially higher and/or responded more quickly in SLH (cold tolerant) than ZH12 (cold susceptible) under low temperature, suggesting they might be crucial contributors during the adaptation of peanut to low temperature. These findings will not only provide valuable resources for study of cold resistance in peanut but also lay a foundation for genetic modification of cold regulators to enhance stress tolerance in crops.